(untitled) (Journal of Educational and Psychological Sciences, 2019)
The aim of the research was to identify the role of extracurricular activities in the emotional and moral development of students at the universities of Aktobe and Orenburg in Prussia and Kazakhstan. To achieve this goal, research was carried out in three stages: Phase I- Analysis and Diagnosis- The stage included the definition of the systematic basis of research and the degree of problem of study in Kazakhstan and Russia, foreign literature and student education, analysis of the main provisions of the normative documents of the legislative, and the characteristics of the main positions of research, conceptual and class system. , Tasks, search hypotheses. At this stage, a number of methods and methods were adopted: analysis of theoretical sources, targeted educational supervision, questionnaire, and experiment testing. Phase II- Model Design- The trial phase during which the work system was conducted on the moral and spiritual composition of the student identity, the reform and preliminary analysis of the received facts was carried out. Search hypothesis selected. The data obtained was analyzed and interpreted. At this stage, a number of methods and techniques have been adopted: modeling, theoretical analysis, information synthesis, questionnaire, testing, skilled and experimental work, and methods of mathematical statistics. Phase III- Summary and Analysis- The stage is characterized by the final analysis of the results received during the skilled and experimental work, its methodology, the generalization, the formulation of research findings, and the recording of research in the form of thesis. The methods used at this stage were: mathematical data processing, tabulation and interpretation of the graph of the results received, comparative analysis. The study sample consisted of (89) respondents from Aktobe University, Orenburg in Russia and Kazakhstan, divided into three groups; two groups and two other groups with 29 students each. The study showed the following results: • Changes were made in a motivational standard and value for spiritual and moral formation: positive positive motives and aspiration for spiritual moral improvement were found in 74.7% of students (compared to 19.5% at the beginning of the experiment). Values ​​measured such as "freedom", "responsibility", "action", "education", "conscience", "mercy". • The student initiative in the social and educational practice of activities for us was an indicator of the positive change of the activity standard. • Extra-curricular activities are integrated in content and techniques and provide mutual enrichment of the spiritual ethical standards of the subject. • Extracurricular activities promote the inclusion of essential aspects of the spiritual and moral formation of the personality at the level of the subjects studied by the student. • The opportunities offered by extracurricular activities allow for the improvement of the spiritual and moral formation of the student, taking into account the requirements of modern science and practice.